2019
DOI: 10.1002/ijc.31960
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating microRNAs with Ago2 complexes to monitor the tumor dynamics of colorectal cancer patients during chemotherapy

Abstract: Because of the different forms of circulating miRNAs in plasma, Argonaute2 (Ago2)‐miRNAs and extracellular vesicles (EV‐miRNAs), we examined the two forms of extracellular miRNAs in vitro and developed a unique methodology to detect circulating Ago2‐miRNAs in small volumes of plasma. We demonstrated that Ago2‐miR‐21 could be released into the extracellular fluid by active export from viable cancer cells and cytolysis in vitro. As miR‐21 and miR‐200c were abundantly expressed in both metastatic liver sites and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
0
15
0
2
Order By: Relevance
“…Circulating cell-free RNAs, like miRNAs, have also been explored as candidates for liquid biopsy in cancer patients [22]. It has been suggested that miRNAs are actively released in the extracellular fluid and in the bloodstream by viable cancer cells [23]. This is particularly interesting in the case of naïve patients because these biomarkers are abundantly released by viable cells before treatment.…”
Section: Liquid Biopsy: History Advantagesmentioning
confidence: 99%
“…Circulating cell-free RNAs, like miRNAs, have also been explored as candidates for liquid biopsy in cancer patients [22]. It has been suggested that miRNAs are actively released in the extracellular fluid and in the bloodstream by viable cancer cells [23]. This is particularly interesting in the case of naïve patients because these biomarkers are abundantly released by viable cells before treatment.…”
Section: Liquid Biopsy: History Advantagesmentioning
confidence: 99%
“…It is thereby possible that the circulating biomarker value of miR-21 comes mostly from its presence in exosomes. Nevertheless, it was recently shown that nonvesicular Ago2-associated miR-21 was actively released from HT29 CRC cell lines and that its levels could surpass those of EV-encapsulated miRNA in the absence of chemical lysis [120].…”
Section: Exosomal Mirnas Influence Crc Tumor Microenvironmentmentioning
confidence: 99%
“…Extracellular miRNAs have two main sources: the miRNAs that cofractionate with Agonaut2 (Ago2) protein complexes which are thought to originate mainly from dead cells and the miRNAs that are released through extracellular vesicles (EV), mainly from viable cells and engaged in intracellular communication [72]. The authors hypothesized that by measuring levels of Ago2 miRNAs and EV miRNAs during chemotherapy, they would be able to assess the response to antitumor therapy.…”
Section: Mirnas Predicting Treatment Response In Crcmentioning
confidence: 99%